2006
DOI: 10.1093/nar/gkl653
|View full text |Cite
|
Sign up to set email alerts
|

Mouse microRNA profiles determined with a new and sensitive cloning method

Abstract: MicroRNAs (miRNAs) are noncoding RNA molecules of 21 to 24 nt that regulate the expression of target genes in a post-transcriptional manner. Although evidence indicates that miRNAs play essential roles in embryogenesis, cell differentiation and pathogenesis of human diseases, extensive miRNA profiling in cells or tissues has been hampered by the lack of sensitive cloning methods. Here we describe a highly efficient profiling method, termed miRNA amplification profiling (mRAP), as well as its application both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 24 publications
5
79
0
1
Order By: Relevance
“…In normal tissues, about 25 to 40% of cloned small RNAs correspond to miRNAs. 19,41 In the case of CLL, miRNAS represented about 10 % of small RNAs and included a total of 13 known miRNAs. This is in agreement with previous reports indicating a reduced accumulation of miRNAs in neoplastic tissues, 19,42 which was associated with an impaired processing of miRNA precursors.…”
Section: Discussionmentioning
confidence: 99%
“…In normal tissues, about 25 to 40% of cloned small RNAs correspond to miRNAs. 19,41 In the case of CLL, miRNAS represented about 10 % of small RNAs and included a total of 13 known miRNAs. This is in agreement with previous reports indicating a reduced accumulation of miRNAs in neoplastic tissues, 19,42 which was associated with an impaired processing of miRNA precursors.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that mRAP readily allows the isolation of 41 Â 10 6 miRNA concatamers from p1 Â 10 4 cells and is thus suitable for miRNA profiling of clinical specimens. 5 Indeed, mRAP functioned well with the small number of purified specimens in the present study, with the result that sequencing capacity, rather than specimen quantity, is likely to be the limiting factor for the size of the final data set in most studies.…”
mentioning
confidence: 65%
“…3 In T-cell acute lymphoblastic leukaemia, ABL1 can be fused with NUP214 (a gene located in 9q34) on episomes 4 or with EML1 by a t(9;14)(q34;q32) translocation. 5 Moreover, a recent publication described a t(1;9)(q24;q34) translocation in a B-cell acute lymphoblastic leukaemia case with a putative RCSD1-ABL1 fusion without molecular confirmation. 6 Here we report the cytogenetic and molecular analysis of a t(9;10)(q34;q23) translocation, from a case of B-lineage ALL, with recombination of ABL1 to a new partner gene, ZMIZ1 (zinc-finger MIZ-type containing 1).…”
Section: Note Added In Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of miRNAs has been shown to be tightly regulated in a developmental stage-dependent, as well as in an organ-dependent, manner (Aboobaker et al 2005;Wienholds et al 2005;Ason et al 2006;Takada et al 2006a), suggesting that they may play important roles in embryonic development and tissue organization. The miRNAs miR-1 and miR-124, for example, are specifically expressed in muscle and the central nervous system, respectively, in zebrafish, medaka, mouse, and fly, suggesting that the function of these miRNAs is conserved across animal phyla .…”
Section: Introductionmentioning
confidence: 99%